The mediating effect of job satisfaction between psychological capital and job burnout of Pakistani nurses - Nazim Ali; Arshad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Low-level of job satisfaction, psychological capital and high level of job burnout is very detrimental both for the organization and individual employee. A few studies have identified the factors influencing job burnout of nurses. The model developed in this study is unique and yet to be used. This study investigates the mediating effect of job satisfaction between psychological capital and job burnout of nurses in Pakistan. Data were collected from 219 female nurses working in government hospitals of Khyber Pakhtunkhwa (KPK), Pakistan through Psychological Capital Questionnaire. Questionnaire is based on a Maslach Burnout Inventory-General Survey and Job Satisfaction Survey. Correlation analysis explored a significant positive relationship between psychological capital and job satisfaction and a negative relationship between psychological capital and job burnout. A significant negative relationship between job satisfaction and job burnout was also confirmed. Confirmatory factor analysis revealed a significant positive path from psychological capital to job satisfaction, and a negative path to job burnout. A significant negative path from job satisfaction to job burnout was also investigated. Furthermore, job satisfaction mediated the relationship between psychological capital and job burnout. The path from psychological capital to job burnout through job satisfaction was found significant. This study contributes to the previous reservoir of literature and explains the importance of the impact of psychological capital on job burnout.
Keywords: 330; psychological capital; job satisfaction; job burnout; nurses